Why technocratic understandings of humanitarian accountability undermine local communities. Issue 2 (17th February 2022) - Aijazi, Omer
ABSTRACT: Current trends in humanitarian accountability are unpacked through the examination of an accountability system put in place after the 2010 monsoon floods in Pakistan. Humanitarian accountability, when narrowly understood as a technical and procedural tool, can undermine local self-advocacy efforts, silence community dissent, and supress broader equity claims. Reframing humanitarian accountability as a political and ethical project can inspire innovation, support frontline aid workers, and ignite the radical revisioning of the humanitarian contract itself.